2014
DOI: 10.1167/iovs.13-12975
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Response of Optic Nerve Head Blood Flow to Increase of Arterial Blood Pressure in Humans

Abstract: The continuous recording of both BP and LDFs represents a novel and more precise approach to the characterization of ONH hemodynamics during isometric exercise, especially useful in the future for patients with ocular diseases. The efficiency of the ONH blood flow autoregulation appears to vary significantly between healthy subjects. (ClinicalTrials.gov number, NCT00874913.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…reported that 2‐min handgripping induced a 43% increase in OPP and an increase of 19% in blood flux (measured by LDF) in the ONH (Chiquet et al. ). Moreover, the effect of autoregulation appears to vary significantly among subjects due to individual variations.…”
Section: Physical Exercise and Ocular Perfusionmentioning
confidence: 99%
“…reported that 2‐min handgripping induced a 43% increase in OPP and an increase of 19% in blood flux (measured by LDF) in the ONH (Chiquet et al. ). Moreover, the effect of autoregulation appears to vary significantly among subjects due to individual variations.…”
Section: Physical Exercise and Ocular Perfusionmentioning
confidence: 99%
“…Retrobulbar (OA, CRA) 30 normals CDI Postural change No difference in velocity or RI in OA but significant difference between OA and CRA (p < 0.01 and p < 0.001) due to significant rises in pulse (p < 0.05) and DBP (p < 0.01) brought on by postural change; fall in RI in CRA with administration of timolol (p < 0.05) with effects independent of any simultaneous decrease in IOP in timolol eye (p < 0.01) [147] Evans et al In the CRA, all three groups had similar changes in EDV and RI, but that only the NTG group had a statistically significant change in PSV from sitting to supine [148] Joos et al indicating that the normal healthy eye is not able to regulate to maintain PCA blood flow velocities in response to these large induced increases in IOP [159] Garhofer et al MFVs lower in SPCA and CRA of OAG; nonlinear relationship between the pulsatility and resistive indices compared to the linear relationship that is seen in normal individuals [166] Shoshani et al [167] Pillunat et al IOP increase with scleral suction cup No significant decrease in blood flow until IOP elevations around 45-55 mmHg in all patients [157] Riva et al IOP increase with scleral suction cup Autoregulation failed at OPP of 10-15 mmHg [158] Weigert et al IOP increase with scleral suction cup In response to a moderate increase in IOP induced by scleral suction cup, there was no significant difference in ocular blood flow response between glaucomatous eyes and controls [160] Schmidl et al Isometric exercise (squatting) MAP, IOP and OPP significantly increased after squatting but no significant change to average blood flow [153] Schmidl et al Isometric exercise (hand gripping) Increase of flow (19%) resulting from an increase in velocity (17%) and volume (6%) was significantly less than predicted for a passive autoregulatory response; efficiency of autoregulation in normal subjects varies [155] Sampolesi et al Therapeutic IOP lowering In more advanced stages of glaucoma, autoregulation is not preserved, and antiglaucoma medications cannot restore normal ONH flow [161] Hafez et al Therapeutic IOP lowering Mean correlation between OPP and flowmetry prior to treatment was small (r = 0.32); it was even smaller after 6 months of IOP lowering (r = 0.15), suggesting that this population of both OAG and OHT patients had deficient autoregulation that was improved by lowering the IOP either with timolol or dorzolamide [162] Feke et al [149] Sehi et al velocity from sitting to supine. The most significant finding of Galambos' results were that the velocities in the SPCA seems tightly controlled in controls with no significant changes in any CDI parameters, where there were significant changes to these hemodynamic parameters in both NTG and POAG patients.…”
Section: Refmentioning
confidence: 99%
“…Movaffaghy et al assessed ocular blood flow using LDF after healthy patients performed squatting exercises and found that, in the face of increased MAP, IOP and OPP, there were no substantial changes to blood flow in the ONH [153]. Subsequent studies using similar methods have corroborated these findings [100,154,155]. Schmidl et al compared autoregulation of blood flow in the choroidal and ONH circulations of healthy subjects using LDF during squatting and during artificial increase in IOP.…”
Section: Isometric Exercisementioning
confidence: 99%
“…In addition, blood pressure was not measured continuously as in a recent study, 80 but was measured every minute only. Furthermore, OPP can only be estimated from measurements of blood pressure and IOP, and the limitations of this approach have been reviewed in some detail recently.…”
Section: Discussionmentioning
confidence: 99%